Pengaruh Nilai-Nilai Keislaman dalam Gurindam 12 terhadap Persepsi Individu - Gherina, Gherina; Larasati, Ananda; Subakti, Zunita (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
In the era of globalization, understanding Islamic valuesin classical literary works such as Gurindam 12 is highlyrelevant, as traditional values are often eroded by changingtimes. This study aims to explore the extent to which thesevalues are understood and internalized by individuals, aswell as their influence on daily behavior. Using acorrelational quantitative approach and questionnaires, thisresearch involves Psychology students at IAIN SAS BangkaBelitung. The results show that the Islamic values inGurindam 12 have a significant influence on individuals#39;perceptions, shaping their worldview and attitudes. Valuessuch as honesty, justice, responsibility, and obedience toGod play a crucial role in shaping individual character andbehavior. These findings emphasize the importance ofpromoting classical literary works in character educationbased on Islamic values.